Family, Friends and Colleagues' Support as Correlates of Job Performance among Non-Teaching Staff of Public Universities in Benue State: Implications for Counselling - Moses Mhide Kpum (Indonesian Institute for Counseling, Education and Theraphy, 2023)
The study investigated how family, friends and colleagues' support as correlates with job performance of non-teaching staff of public universities in Benue State for counselling implications. The study adopted a correlation research design. The population comprises 2,703 non-teaching staff from three public universities in Benue State: Joseph Sarwuan Tarka University in Makurdi, Benue State University in Makurdi, and the Federal University of Health Sciences in Otukpo. The sample size for the study was 348 non-teaching staff. The sample was selected using proportionate stratified and accidental sampling techniques. The instrument for data collection was a structured questionnaire titled “